Comprehensive Transcriptomic and Metabolomic Analysis of the Litopenaeus vannamei Hepatopancreas After WSSV Challenge - Yu, Dianjiang; Zhai, Yufeng; He, Peimin; Jia, Rui (Frontiers in Immunology, 2022)
Litopenaeus vannamei is the major farmed shrimp species worldwide. White spot disease due to white spot syndrome virus (WSSV) is severely affecting shrimp worldwide, causing extensive economic losses in L. vannamei culture. This is the first study that applied combined transcriptomic and metabolomic analysis to study the effects on the L. vannamei hepatopancreas after WSSV challenge. Our transcriptomic data revealed differentially expressed genes (DEGs) associated with immunity, apoptosis, the cytoskeleton and the antioxidant system in the hepatopancreas of L. vannamei. Metabolomic results showed that WSSV disrupts metabolic processes including amino acid metabolism, lipid metabolism and nucleotide metabolism. After challenged by WSSV, immune-related DEGs and differential metabolites (DMs) were detected in the hepatopancreas of L. vannamei, indicating that WSSV may damage the immune system and cause metabolic disorder in the shrimp. In summary, these results provide new insights into the molecular mechanisms underlying L. vannamei’s response to WSSV.